European Insolvency Proceedings : Commentary on Regulation (EU) 2015/848 of the European Parliament and of the Council of 20 May 2015 on Insolvency Proceedings (Recast) /: Commentary on Regulation (EU) 2015/848 of the European Parliament and of the Council of 20 May 2015 on Insolvency Proceedings (Recast). (2021) - Unknown
No abstract available